Mewujudkan Reproductive Health Awareness pada Remaja melalui Edukasi Kesehatan Reproduksi - Wardani, Endah Kusuma; Asih, Fransisca Retno (Journal of Health Innovation and Community Services, 2022)
Background: Adolescence is a period of transition from children to adults which is part of the process of growth and development, marked by changes in physical, psychological, and social with an age range of 10-24 years and not married. The typical nature of teenagers who have great curiosity, likes challenges often makes teenagers take action without being based on careful consideration, one of which is reproductive health. Reproductive health is a state of complete physical, mental and social health, not merely free from disease or disability related to reproductive systems, functions and processes. Objective of this community service is to be able to assist adolescents in making decisions when the right age is for them to marry and have children, and adolescents become aware of their reproductive health. Method used is by providing reproductive health education online on the GKJW Banyuwangi youtube channel in June 2021, followed by anthropometric measurements of LiLA, Height, Weight, and BMI calculations. Results of the activity showed that there were still teenagers who did not know about their reproductive health and when anthropometric measurements were carried out, it was found that there were still teenagers whose LiLA and BMI were not ideal. Conclusion: This activity can increase adolescent awareness in making decisions in choosing how to maintain their reproductive health. In addition, it is hoped that the Banyuwangi GKJW youth will also be able to share the education they have received with their peers.